2018
DOI: 10.1186/s12931-018-0860-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of radiological pleuroparenchymal fibroelastosis pattern in interstitial lung disease patients registered for lung transplantation: a retrospective cohort study

Abstract: BackgroundRadiological pleuroparenchymal fibroelastosis (PPFE) lesion is characterized by pleural thickening with associated signs of subpleural fibrosis on high-resolution computed tomography (HRCT). This study evaluated the clinical significance of radiological PPFE as an isolated finding or associated with other interstitial lung diseases (ILDs) in patients having fibrotic ILDs and registered for cadaveric lung transplantation (LT).MethodsThis retrospective study included 118 fibrotic ILD patients registere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…The radiological criteria for PPFE, modified from Reddy et al . 's criteria and other articles, were defined as follows: (i) bilateral subpleural dense fibrosis with or without pleural thickening in the upper lobes, (ii) confirmation of disease progression (defined as an increase in the upper lobe consolidation with or without pleural thickening and/or a decrease in upper lobe volume on serial radiological assessment) and (iii) exclusion of other identifiable aetiologies (such as history of radiation therapy in the upper lung zones and active pulmonary infection) or HRCT findings such as multiple lung or pleural calcification and unilateral lesion. Patients were classified as definite PPFE cases if all criteria were met and as possible PPFE cases if criteria (i) and (iii) were met.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The radiological criteria for PPFE, modified from Reddy et al . 's criteria and other articles, were defined as follows: (i) bilateral subpleural dense fibrosis with or without pleural thickening in the upper lobes, (ii) confirmation of disease progression (defined as an increase in the upper lobe consolidation with or without pleural thickening and/or a decrease in upper lobe volume on serial radiological assessment) and (iii) exclusion of other identifiable aetiologies (such as history of radiation therapy in the upper lung zones and active pulmonary infection) or HRCT findings such as multiple lung or pleural calcification and unilateral lesion. Patients were classified as definite PPFE cases if all criteria were met and as possible PPFE cases if criteria (i) and (iii) were met.…”
Section: Methodsmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF) is characterized by a UIP pattern on high‐resolution computed tomography (HRCT) or surgical lung biopsy and has a poor prognosis with frequent complications such as pneumothorax . There have been some reports on the clinical significance of PPFE in IPF patients . Oda et al ., in 110 patients with biopsy‐proven IPF, showed that those with histologically confirmed PPFE ( n = 9) had different clinical features than those without (IPF alone, n = 99); the PPFE group showed a significantly higher residual volume, higher partial pressure of carbon dioxide in arterial blood (PaCO 2 ), higher complication rate of pneumothorax and pneumomediastinum and numerically shorter survival time (31.5 vs 82.1 months, P = 0.13) than the no‐PPFE group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanizawa et al [21] reported that, in 118 patients with fibrotic ILD who registered for lung transplantation, BMI was significantly different between the radiologically defined PPFE and no PPFE groups (15.9 kg/m² vs. 21.5 kg/m², p < 0.001). Oda et al [16], in 108 IPF patients, reported that the combined PPFE group showed lower BMI (18.6 ± 1.8 kg/m² vs. 25.1 ± 3.6 kg/m², p < 0.01) and higher RV/TLC (42.6% ± 8.7% vs. 33.1% ± 7.6%, p < 0.01) than the IPF only group.…”
Section: Discussionmentioning
confidence: 99%
“…Although it reported that the median survival time for CTD-ILD patients was roughly 6.5 years, and the mortality rate due to CTD attributable to ILD was approximately 123.6 per 1000 person years [2,3], but the progression and prognosis of CTD-ILD varies widely between individuals [4]. In general, the poor prognosis of ILD was reported to correlate with the dyspnea score, pulmonary function degree [5,6], patterns of high-resolution computed tomography (HRCT) scans [7,8]. Limited by the patient's cooperation, we try to find some reliable and less expensive serum biomarkers which are also easy to detect.…”
Section: Introductionmentioning
confidence: 99%